Development of Interactive Learn Pengembangan Media Pembelajaran Interaktif IPAS Berbantuan Genially Berbasis Model Discovery Learning Untuk Meningkatkan Hasil Belajar Kognitif Peserta Didik Di Kelas III Sekolah Dasar: Pengembangan media pembelajaran interaktif IPAS menggunakan Genially berbasis Model Discovery Learning - Pitaloka, Sinta; Widi Winarni, Endang; Muktadir, Abdul (Jurnal Kajian Pendidikan Dasar, 2025)
The purpose of this study was to develop, describe the characteristics, logical feasibility, user response and effectiveness of learning media using Genially based on Discovery Learning to improve high-level cognitive learning outcomes of students in grade 3 of elementary school 28 Seluma. The type of research used was R&D (Research and Development) research with the ADDIE development model. The types of data used were qualitative and quantitative data using instruments in the form of interviews, needs analysis questionnaires, expert validation sheets, and user response questionnaires. The results showed that Genially learning media was able to improve student interactivity. Logically, Genially learning media is feasible to use based on the results of material validation 0.95 language experts 0.95 media/design experts 1.0 which is a high validity category. User responses showed a percentage of 100% of the attractiveness of Genially learning media. The response of users of Genially learning media is very high, this is indicated by the average of the N-Gain test of 85.02 which is included in the effective category. So it can be concluded that the use of Genially learning media is able to improve high-level cognitive learning outcomes of class III students at state elementary school 28 Seluma.